Repeatability of Peripheral Artery Tonometry in Female Subjects. (20th October 2013) - Degnan, Andrew J.; Shah, Nandini; Carty, David M.; Petrie, John R.; Delles, Christian; Schneider, Markus P.
Abstract : Background. Peripheral arterial tonometry (PAT) is a novel, non-invasive and operator-independent method for simultaneous assessment of endothelial function and arterial stiffness. We examined the repeatability of PAT in females and the influence of the estrous cycle. Methods. In 14 healthy female and five healthy male control subjects, PAT was performed on three separate occasions with 10 days between visits. Reactive hyperemia index (RHI), a measure of endothelial function, and peripheral augmentation index (AIx), a measure of arterial stiffness, were determined with the EndoPAT-2000 system. Intraclass correlation coefficient (ICC) was calculated as a measure of repeatability. Results. In both female and male groups, RHI and AIx did not differ between the three measurements (all n.s. by 1-way ANOVA). In females, reanalyzing the data after taking phase of estrous cycle into account had no effect on the results. Repeatability for RHI and AIx in females (ICC for RHI = 0.43, ICC for AIx = 0.78) was similar to that in male subjects (ICC for RHI = 0.42, ICC for AIx = 0.63). Conclusions. PAT measurements were not affected by the estrous cycle in females, and repeatability was comparable to that in males. This should facilitate inclusion of female subjects into vascular function studies using PAT.